Phase transitions in food production technologies - Sokolenko, Anatoly; Shevchenko, Oleksandr; Vasylkivskyi, Kostyantyn; Koval, Olga; Maksymenko, Iryna; Shevchenko, Anastasiia (My University, 2020)
The paper deals with information about the general state of technologies for the utilization of secondary energy resources and environmental resources.The analysis of isoenthalpy drying processes led to the conclusion that it is expedient to keep the total potential of the vapor-gas mixture in closed circuit, but with the feature that the drying potential of the medium will be renewable.
Keywords: transition; transformation; circuit; exchange; condensation; кафедра мехатроніки та пакувальної техніки; кафедра процесів і апаратів харчових виробництв; кафедра технології хлібопекарських і кондитерських виробів; кафедра готельно-ресторанної справи